(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
Sports are an independent type of human activity, which plays an important role in the development of society. They have a vital impact on social production, the development of social relations, the formation of a person as a person. In this article, the author describes in detail the role of sports in public life.